Research on The Control of Out-of-Round Wheel Profiles of High-Speed Railway Derived From Numerical Simulations - Song, Ying; Wang, Zhichen (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Periodic non-roundness of railway wheels will cause a series of variety on vehicle/track coupling system dynamic responses. A coupling dynamics model of railway vehicle with out-of-round wheels and track was built based on ADAMS/Rail. The effect of periodic non-roundness of wheel on the dynamical behavior of the vehicle system was analyzed. The numerical results regarding the misalignments of the vehicle and wheelset, the vertical wheel/rail contact forces and the reduction in the wheelset loading are presented under the conditions in which the wheels are in out-of-round and the train speed is from 200 km/h to 350 km/h. The results show that the dynamical vertical wheel/rail interaction forces are much related to the wheel out-of-roundness status. The critical range of the wheel out-of-roundness is determined according to the traditional criterion of wheelset loading reduction for safely running estimation. Itâ??s pointed out that out-of-round railway wheels can be detected by wheel/rail interaction force real-time monitoring system to guarantee safety and to minimize costs for repair and maintenance.